IMPLEMENTASI NILAI EKONOMI PANCASILA PADA KOPERASI TRI CIVITAS FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS LAMBUNG MANGKURAT - Latipah, Nur; Rabiatul Adawiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Pancasila-based economics is a fundamental framework in shaping a just and equitable economic system oriented toward collective welfare. Cooperatives, as the embodiment of economic democracy, play a strategic role in implementing Pancasila values in economic activities. However, the dynamics of modern economic practices and organizational constraints often influence the optimal realization of these values. This study aims to analyze the implementation of Pancasila economic values in the management of Koperasi Tri Civitas, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, as well as to identify the supporting and inhibiting factors. This research employs a qualitative approach with data collection techniques including interviews, observation, and documentation involving supervisors, administrators, employees, and cooperative members. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that the implementation of Pancasila values has been carried out in various aspects of cooperative management. The value of divinity is reflected in honesty, trustworthiness, and responsibility in financial management. The value of mutual cooperation is evident in collaboration among members and administrators. The value of kinship is shown through harmonious relationships and open communication, while the value of justice is implemented proportionally based on members’ contributions. Furthermore, the principles of Pancasila economics are applied through non-discriminatory services and the distribution of surplus (SHU) based on participation levels. Despite these efforts, challenges such as low member participation and limited managerial time remain. Therefore, strengthening the implementation of Pancasila economics is necessary to achieve more optimal cooperative performance.